ISLAMIC DEVELOPMENT ECONOMY: An Introduction - Rizal Akbar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
In recent years, Islamic economy grows fast both theoretically and practically. The establishment syariah financial institutions, Islamic bank, insurance, and even Islamic obligation is a practical phenomenon. However, the development of Islamic economy is only concentrated in financial sectors. As a result, there is less attention toward the discourses of poverty, backwardness, and marginal areas.An effort to formulate Islamic approaches in development economy is hoped as an early step to answer the failure of some conventional development approaches. This paper aims to start this work by trying to spread out the basic understanding of development economy analyzed using Islamic principles, and it introduces a methodology which must be developed so that it is hoped that a study of Islamic development economy could be implemented comprehensively.